Effect of chromium and titanium on the microstructure and mechanical properties of cast steel - Białobrzeska, Beata; Jasiński, Robert; Dziurka, Rafał; Bała, Piotr (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
In this work, the influence of chromium and titanium on the microstructure and mechanical properties of cast steel is investigated. The analysis was carried out on a material covered by patent Pat.243157. Advanced techniques were used, including dilatometric analysis, light microscopy (LM), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The material was examined in various states: as-cast, quenched, and quenched with subsequent tempering at 200 °C, 400 °C, and 600 °C. Important mechanical properties such as hardness, yield strength, percentage elongation, percentage reduction in area after fracture, and impact toughness at temperatures ranging from -40 °C to +20 °C were evaluated. The results were compared with those of a reference cast steel without these alloying elements, allowing a detailed assessment of the influence of chromium and titanium. The investigation begins with a comprehensive literature review of the effects of these elements in iron-based alloys. The results highlight the influence of chromium and titanium on the mechanical properties and microstructural development of cast steel. These elements play a critical role in enhancing mechanical strength, particularly after quenching and tempering, although there are evident trade-offs in ductility and impact toughness. In addition, the study discusses the damage mechanisms, focusing on the role of titanium nitrides in the cracking process.
Keywords: cast steel, titanium, chromium, heat treatment, microstructures, mechanical properties